2018
DOI: 10.1155/2018/1512830
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Using Nanoparticles of SiO2 to Improve the Performance of Recycled Aggregate Concrete

Abstract: e aim of this paper was to examine the feasibility of using nanoparticles of SiO 2 (nanosilica) to improve the performance of recycled aggregate concrete (RAC) containing recycled aggregate (RA) derived from processing construction and demolition waste of concrete buildings. e examined properties include compressive strength, splitting tensile strength, and water absorption. e study also includes examining the microstructure of RA and RAC with and without nanoparticles of SiO 2 . In total, nine mixes were inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 36 publications
1
36
0
Order By: Relevance
“…The strength enhancement of the RAC due to the utilization of SF can be mainly attributed to the pozzolanic reaction and partly to the filling capability of this material because of it very small particles [20]. The chemical reaction of the SF (pozzolanic reaction) can result in more calcium silicate hydrate gel; resulting in a stronger concrete [6] [13] [11]. Furthermore, owing to its fine-particles, silica fume has the potential to play a crucial role in filling the micro-voids and pores of the surface of the RCA and in adjusting the microstructure of the concrete; hence leading to denser concrete.…”
Section: Results Of Compressive Strengthmentioning
confidence: 99%
See 2 more Smart Citations
“…The strength enhancement of the RAC due to the utilization of SF can be mainly attributed to the pozzolanic reaction and partly to the filling capability of this material because of it very small particles [20]. The chemical reaction of the SF (pozzolanic reaction) can result in more calcium silicate hydrate gel; resulting in a stronger concrete [6] [13] [11]. Furthermore, owing to its fine-particles, silica fume has the potential to play a crucial role in filling the micro-voids and pores of the surface of the RCA and in adjusting the microstructure of the concrete; hence leading to denser concrete.…”
Section: Results Of Compressive Strengthmentioning
confidence: 99%
“…Crushed concrete, for example, can be used as recycled coarse aggregate in the concrete manufacture. This is also very helpful in conserving our environment [5] [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential of nano-technology in enhancing the performance of concrete and developing novel, sustainable, advanced cement composites with unique mechanical, thermal, and electrical properties is promising [35]. For example, nano-SiO2 (NS) particle as the most popular nanomaterial mixture in concrete modification provided an excellent performance in improving the mechanical properties and durability of NAC [20,[38][39][40]. Studies have shown that the addition of NS in fresh concrete resulted in 21.6% increase of compressive strength [38], and changed the microstructures by filling the voids of each content of concrete mixture physically and helping form the C-S-H crystal nucleus of cement paste, which in turn changed the physical properties and durability of concrete mixture [36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Hoffmann et al [ 155 ] have also highlighted that the RCA was suitably used in a wide variety of reinforced concrete members. Numerous studies have attempted to relate the inferior properties of RCA concrete to the weak interfacial transition zone between the recycled aggregate and the new cement paste [ 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 ], which is mainly attributed to the old layer of mortar adhered to the surface of aggregate [ 164 ] that is characterized by loose, porous and micro-cracked surface [ 159 , 165 ]. In their study Han et al [ 166 ] stated that the RC beams with 100% RCA showed larger deflection and less shear strength than the control beams with virgin aggregate.…”
Section: Literature Reviewmentioning
confidence: 99%